Isolation and Identification of Biosurfactant Producing Bacteria from Contact Pond Pond WWTP Palm Oil Industry - Herman Syahputra Tambunan; M. Hasbi M. Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis study aims to obtain biosurfactant producing bacteria originating from the pond mud of IPAL in the palm oil industry at PT. Sawit Asahan Indah, Ujung Batu, Rokan Hulu, Riau Province. This study uses a survey method. Mud samples are taken from the Contact pond by using a sample bottle, then inserted into the cool box, then taken to the laboratory. Furthermore, 5 gramsof mud samples were weighed and sample dissolution was carried out using BPS (Buffer Phosphate Saline) media. Furthermore, this sample was enriched with BHI(Brain Heart Infusion) media, then incubated for 1x24 hours. Furthermore, this sample was diluted using 0.98% NaCl until a dilution of 10-6, and calculated the number of bacteria growing, using Petrifilm at 10-4, 10-5 and 10-6 dilutions. Then bacterial planting and purification were carried out using the media of Blood Agar and MacConkey Agar. Then, it was identified using biochemical tests andPCR (Polymerase Chain Reaction) tests. The results found 3 types of bacterial isolates with 2 biosurfactant producing species, Proteus mirabilis, and Providencia stuartii. Then it is known the rank ofDNA from bacterial species that have the highest Emulsification Index, namely 100% Proteus mirabilis.Keywords: Oil contamination, Biochemical Test, PCR test, Proteus mirabilis and Providencia stuartii